2021
DOI: 10.1111/bjso.12485
|View full text |Cite
|
Sign up to set email alerts
|

Self‐objectification in women predicts approval motivation in online self‐presentation

Abstract: Researchers have examined self‐objectification – viewing oneself as an object rather than a subject – in terms of its impact on intrapersonal factors, such as mental health and cognitive performance. However, few have examined how self‐objectification relates to interpersonal factors. The present research addressed this gap by testing the impact of self‐objectification on social approval motivation among women. Study 1 (n = 103) found that individual differences in self‐objectification correlated positively wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 121 publications
(117 reference statements)
0
5
0
1
Order By: Relevance
“… 69 , 70 The visual self-presentation is especially important for the self-expression of women. 71 This could at least partly explain the dominance of Instagram use in our study.…”
Section: Discussionmentioning
confidence: 74%
“… 69 , 70 The visual self-presentation is especially important for the self-expression of women. 71 This could at least partly explain the dominance of Instagram use in our study.…”
Section: Discussionmentioning
confidence: 74%
“…Studies have found consistent evidence that self-objectification is positively associated with selfie-editing behaviors, which reflect strategic self-presentation (Chen et al, 2022; Fox et al, 2021; Salomon & Brown, 2020; Wang et al, 2021). For example, Caso et al (2020) found a positive correlation between self-objectification and the frequency of posting and editing selfies.…”
Section: Self-objectification and Online Self-presentationmentioning
confidence: 86%
“…Saguy et al (2010) explained their findings by suggesting that self-objectifying women may try to appear more aligned with traditionally feminine roles in interactions (e.g., by being agreeable and submissive; Rudman & Glick, 2001). Viewed from an approval-seeking perspective, this finding may reflect women's attempt to act according to their perceptions of others’ preferences (Chen et al, 2022). Thus, these findings enrich the literature on self-objectification and its interpersonal consequences by showing how self-objectifying women are driven by their need for social approval to present more socially desirable selves in social media activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Items with the correct codes were reversed. Body Shame Subscale, of Objectified Body Consciousness Scale is developed by McKinely and Hyde (1996), is composed of 8 items totally, with 7-point Likert scale, ranging from strongly disagree (1) to strongly agree (7). The body shame scale is a reliable having alpha coefficient .87.…”
Section: Objectified Body Consciousness Scalementioning
confidence: 99%